The Role of Female Directors on Probability of Financial Distress - Bella Christinna Santosa; Tania Gianina; Yang Elvi Adelina; Vania Pradipta Gunawan (Universitas Prasetiya Mulya, 2022)
This study aims to determine the effect of female directors on the probability of financial distress in companies listed on the Indonesia Stock Exchange from 2016 to 2021, except the financial industry with the total number of company’s data observations is 2,840 observations. The study used binary logistic regression analysis and penalized maximum likelihood. The results of the study found that female directors do not affect the probability of financial distress in the company. A robustness test is also conducted to compare the consistency of the results between SOEs and non-SOEs with the number of observations for each type of company are 114 observations and 2,726 observations. The findings are consistent, showing that female directors have no effect on the likelihood of financial distress in SOEs or non-SOEs. Therefore, this study could provide practitioners with updated understandings and perspectives regarding the existence of female directors in companies that shows the proportion of female directors is still low so the effect on the probability of a company's financial distress has not been seen.